CIRC-b-FCL Model for Teaching Intermediate Reading in COVID-19 Era (A Study on the Validity of the Model) - Eka Sustri Harida; Jufrizal; Hermawati Syarif; Ratmanida (International Journal on Integrated Education, 2021)
English Language Teaching (ELT) in the pandemic Corona Virus Disease 2019 (COVID-19) faced the problems. The teaching-learning process cannot be done directly in the classroom. Based on this phenomenon, a new model of teaching was introduced to solve this problem. The purpose of this writing is to describe the validity of the new model, Cooperative Integrated Reading and Composition based Flipped Classroom Learning (CIRC-b-FCL) in teaching intermediate reading for university students in the COVID-19 era. A qualitative approach was done in this research, and the validity instrumentation was being used to evaluate the model. Data were analyzed by reduction, display, and interpretation. Based on the findings, it was known that the model was valid and reliable. It is known from the score given by all validators; it was 4.51 (valid and can be used without revision) with the percentage of 90% that is with interpretation very valid. Based on the result, it was assumed that the model, CIRC-b-FCL, was very valid and reliable to be implemented in the teaching and learning process of university students in intermediate reading classes for understanding paragraph. However, it needs more analysis on the use of the model purely online to support the 5.0 technology, because this research is not seen from the aspect of fully online, but in the blended system.